EKSPRESI KORESEPTOR HUMAN IMMUNODEFICIENCY VIRUS CCR5 DAN CXCR4 PADA SUBSET SEL LIMFOSIT T SERTA MONOSIT - Agnes Rengga Indrati; Hinta Meijerink; Herry Garna; Bachti Alisjahbana; Ida Parwati; Reinout van Crevel; Andre van der Venn (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
Chemokine receptors CCR5 and CXCR4 which lied on lymphocyte cell surface play important role in HIV infection and pathogenesis.The expression of these chemokine receptors will affect progressively the disease. The objectives of the study are to find the distributionof lymphocyte T cell subset and monocyte among the peripheral blood mononuclear cells and to know the determination of CCR5 andCXCR4 co receptors expression on T lymphocyte cells subset and monocyte. This study is a preliminary study to explore the distributionof co receptors CCR5 and CXCR4 expression in healthy people. The sample taken is peripheral blood mononuclear cells (PBMC) fromhealthy subjects. The identification of T lymphocyte cells subsets and monocyte, and the expression of CCR5 and CXCR4 co receptorswere determined using flowcytometry. The memory T cell (CD4+CD45RO) is found to be the largest proportion among T lymphocyte cell(66.2%), whereas the other T lymphocyte cell subset, regulatory T cell, which identified by CD25+ high expression was found between2.0-5.3% from the whole T lymphocyte cell. The proportion of CXCR4 co receptors was found higher compare to CCR5 co receptorson all T lymphocyte subsets and monocyte. Only small proportion of monocyte expresses both co receptors (2.85%), but most of the Tlymphocyte cell expressed both CCR5 and CXCR4. The expression of the CXCR4 on regulatory T cell (18.18%) is the lowest compared toother cells, but the fluorescence intensity of both co receptors was very high (CCR5 53.53 and CXCR4 49.33). The different distributionof CCR5 and CXCR4 co receptors among T lymphocyte cell subsets and monocyte will influence the vulnerability and the pathogenicityof HIV infection.